Current practice with grafts with multiple renal arteries in kidney transplantation: role of the methylene blue in the lower pole - Cherchi, Vittorio; Baccarani, Umberto; Ventin, Marco; Pravisani, Riccardo; Puggioni, Alessandro; Zanini, Victor; Lorenzin, Dario; Vetrugno, Luigi; Risaliti, Andrea; Terrosu, Giovanni; Adani, Gian Luigi (Acta Biomedica Atenei Parmensis, 2022)
Kidneys with multiple renal arteries (MRAs) from different patches, may provide to the surgeon additional technical difficulties that make kidney transplants very challenging. MRAs have been largely debated over the years whether to be anastomosed or not due to the disappointing outcomes when it comes to inappropriate ligation or anastomosis.  Some authors empirically reassure that smaller branches can be safely ligated and dissected without intraoperative and postoperative complications or compromising the functional recovery of the graft. Literature is poor about the possible differences in the management of superior and inferior polar arteries. Inferior polar arteries represent a topic of great interest as they may also supply the proximal ureter.The aim of this article is to merge the current knowledge about the management of inferior polar arteries and to highlight if there is any role of the methylene blue dye (MB) in the study of the ureteral vascularization in kidney transplantation.MB can be considered a safe and simple tool of vascular perfusion assessment in kidney transplantation. By injecting the dye-solution into the inferior MRA hidden ureteral branches can be unmasked and guide the surgeon to preserve important vessels.In view of their fundamental role in the vascularization of the ureter, the lower polar arteries of the graft, should be invariably studied by MB. It provides an objective, simple and fast tool for the evaluation of the ureteral vascularization when injected through the inferior MRA of the graft.